Knowledge-Driven Economy As A Panacea For Economic Recession - Eke, Ukeh Micheal; Ani, Wilson (Archives of Business Research, 2019)
Recession and its attendant consequences are not new phenomena in the history of the world economy. In the advanced economies “knowledge” is fast becoming a strategic asset for combating recession and spurring economic development. Technological advances and globalization are gathering pace. For countries tapping in to the ideas, innovations and technologies that abound in a knowledge driven economy, there is a definite abundance of wealth and opportunities for all their people. The study identified the key issues of knowledge based economy; strategies that make a knowledge driven economy the panacea for economic recession, challenges and prospects. The study recommended among others the enthronement of an economic and institutional regime that would help articulate the strategies for easy transition to a knowledge economy, the development of an educated and skilled population with dynamic information infrastructure and effective innovation system and the development of the political and institutional will to effectively implement innovation, education and ICT strategies for better result.